Epistemologi : Rasionalisme, Empirisme, Kritisisme, Pragmatisme Positivisme dan Positivisme Logis - Salsabila Rizma; Eva Dewi (Universitas Maritim AMNI Semarang, 2024)
Epistemology in Philosophy, Epistemology comes from the Greek words, namely epistememe = knowledge and logos = words, thoughts, knowledge. Epistemology aims to critically examine the logical presuppositions and conditions that underlie the possibility of knowledge and tries to provide rational accountability for its claims to truth and objectivity. Rationalism is a philosophical ideology which states that reason is the most important tool for gaining knowledge and gaining knowledge. If empiricism says that knowledge is obtained by experiencing empirical objects, then rationalism teaches that knowledge is obtained by thinking. The tools in thinking are logical rules or logical rules.